Pigmentary retinopathy can indicate the presence of pathogenic LAMP2 variants even in somatic mosaic carriers with no additional signs of Danon disease. Issue 1 (13th June 2020) - Kousal, Bohdan; Majer, Filip; Vlaskova, Hana; Dvorakova, Lenka; Piherova, Lenka; Meliska, Martin; Langrova, Hana; Palecek, Tomas; Kubanek, Milos; Krebsova, Alice; Gurka, Jiri; Stara, Veronika; et al.
Abstract: Purpose: Danon disease (DD) is a rare X‐linked disorder caused by pathogenic variants in LAMP2 . DD primarily manifests as a severe cardiomyopathy. An early diagnosis is crucial for patient survival. The aim of the study was to determine the usefulness of ocular examination for identification of DD. Methods: Detailed ocular examination in 10 patients with DD (3 males, 7 females) and a 45‐year‐old asymptomatic female somatic mosaic carrier of a LAMP2 disease‐causing variant. Results: All patients with manifest cardiomyopathy had pigmentary retinopathy with altered autofluorescence and diffuse visual field loss. Best corrected visual acuity (BCVA) was decreased (<0.63) in 8 (40%) out of 20 eyes. The severity of retinal pathology increased with age, resulting in marked cone‐rod involvement overtime. Spectral‐domain optical coherence tomography in younger patients revealed focal loss of photoreceptors, disruption and deposition at the retinal pigment epithelium/Bruch's membrane layer (corresponding to areas of marked increased autofluorescence), and hyperreflective foci in the outer nuclear layer. Cystoid macular oedema was seen in one eye. In the asymptomatic female with somatic mosaicism, the BCVA was 1.0 bilaterally. An abnormal autofluorescence pattern in the left eye was present; while full‐field electroretinography was normal. Conclusions: Detailed ocular examination may represent a sensitive and quick screening tool for the identification of carriers of LAMP2 pathogenic variants, even in somatic mosaicism. Hence, further investigation should be undertaken in all patients with pigmentary retinal dystrophy as it may be a sign of a life‐threatening disease.